Inter- and Intraobserver Agreement in CT Characterization of Nonaneurysmal Perimesencephalic Subarachnoid Hemorrhage - Brinjikji, W.; Kallmes, D.F.; White, J.B.; Lanzino, G.; Morris, J.M.; Cloft, H.J (American Journal of Neuroradiology, 2010)
BACKGROUND AND PURPOSE: The perimesencephalic pattern of SAH as seen on unenhanced CT is associated with significantly better outcomes when compared to an aneurysmal pattern of SAH. The aim of this study was to determine the degree of inter- and intraoberver agreement for characterization of the NAPH as seen on unenhanced CT. MATERIALS AND METHODS: We retrospectively reviewed the CT scans of 37 patients with spontaneous SAH, all of whom had undergone CT within 24 hours of onset of headache symptoms. All patients had undergone conventional cerebral angiography to confirm or exclude aneurysms or other vascular pathology. All 37 cases were angiographically confirmed nonaneurysmal SAHs. Four readers with neuroradiology subspecialty training independently evaluated CT images to characterize the hemorrhage pattern as compatible with the well-described NAPH. Each reader performed a second reading session blinded to the initial readings. The first and second sets of readings were performed approximately 4 months apart. Inter- and intraobserver agreement for characterization of the NAPH was determined by using the κ statistic. RESULTS: Of the 37 angiographically confirmed nonaneurysmal SAHs, there was unanimous agreement as to the hemorrhage pattern in 29 (78%) cases and disagreement in 8 (22%) cases. Overall, intraobserver agreement was good (κ = 0.80). Interobserver agreement was also good (κ = 0.79). CONCLUSIONS: Overall, inter- and intraobserver agreement for the NAPH was good. There was, however, a level of disagreement among observers, thus suggesting that clinicians should be cautious when deciding whether to pursue follow-up imaging. CTACT angiographyDSAdigital subtraction angiographyNAPHnonaneurysmal perimesencephalic subarachnoid hemorrhageSAHsubarachnoid hemorrhage